1998
DOI: 10.1136/jnnp.64.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Auditory hallucinations in Parkinson's disease

Abstract: Whereas visual hallucinations are often found among patients with Parkinson's disease, the occurrence of auditory hallucinations has never been systematically documented. The occurrence, past and present, of auditory hallucinations has been studied in 121 consecutive patients with Parkinson's disease attending a movement disorders clinic. The cognitive state was evaluated using the short mental test (SMT).Hallucinations were reported for 45 patients (37%); 35 (29%) had only visual hallucinations and 10 (8%) bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 9 publications
6
116
0
6
Order By: Relevance
“…One of the reasons may be that, among the various psychiatric symptoms in Parkinson's disease, visual hallucination is frequent but auditory hallucination has been thought to be rare. However, Inzelberg et al examined 121 cases with Parkinson's disease and reported auditory hallucination in ten cases (7). In the present examination, we found six cases with auditory hallucination among 83 patients.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…One of the reasons may be that, among the various psychiatric symptoms in Parkinson's disease, visual hallucination is frequent but auditory hallucination has been thought to be rare. However, Inzelberg et al examined 121 cases with Parkinson's disease and reported auditory hallucination in ten cases (7). In the present examination, we found six cases with auditory hallucination among 83 patients.…”
Section: Discussionsupporting
confidence: 45%
“…Hallucinations are common symptoms in these patients. Visual hallucinations are a well recognized problem in patients with Parkinson's disease (3)(4)(5)(6), whereas auditory hallucinations are less common (7)(8)(9). As a result, information about the mechanism of auditory hallucinations in Parkinson's disease is not generally available.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, tuberculosis can produce tumor-like lesions in the brain, as some have speculated caused Joan of Arc's voices (Ratnasuriya, 1986). Auditory hallucinations have also been reported in conjunction with Parkinson's disease (Inzelberg, Kipervasser & Korczyn, 1998), migraine headaches (McAbee & Feldman-Winter, 1999), and thyroid conditions (Pearce & Walbridge, 1991).…”
Section: Situational Stressmentioning
confidence: 99%
“…VH are by far the most common hallucinations in PD and LBD although acoustic [46] and haptic (tactile) hallucinations are reported in variable percentages of patients (11-19%). Olfactory hallucinations have also been described recently and open to debate is the question whether somatic complaints which are often reported by patient with PD and DLB [47] actually represent a form of somatic hallucinations.…”
Section: Vh In Pd and Lewy Body Dementiasmentioning
confidence: 99%